A Model of Cultural Appropriation Through The Indonesian Cultural Festival in Guilin, China - Silvester Rilo Pangestu; Nanang Endrayanto (International Journal Labs, 2026)
The Indonesian Cultural Festival (FKI) is an annual activity organised by Indonesian students in Guilin, China. This annual event features various forms of Indonesian cultural performance, including dance, music, drama, traditional games, and culinary arts. The festival not only showcases Indonesian art and tradition, but also creates a space for interaction that facilitates cultural exchange. This study examines the model of cultural appropriation through the Indonesian Cultural Festival in Guilin, China. The theoretical framework draws on Richard Schechner's Performance Theory and Homi Bhabha's concept of the